Commentary on "The deterministic condition for the ground reaction force acting point on the combined knee valgus and tibial internal rotation moments in the early phase of cutting maneuvers in female athletes" - Schilaty, N. D.; Bates, N. A. (Journal of Sport and Health Science, 2024)
For decades, substantial disagreement has persisted as to whether dynamic knee valgus is the cause of the majority of anterior cruciate ligament (ACL) injuries or rather the result of the ACL rupture.1 Consequently, great effort and expense has gone into capturing 3-dimensional kinetics and kinematics from live athletes to drive in vitro and in silico models of ACL injury in order to elucidate the actual mechanism of injury, as these factors have been demonstrated to be surrogates of intraarticular structural loading on the ACL.2,3 The elucidation of injury mechanisms for non-contact ACL injuries is of great medical value as such knowledge consequently permits quantified examination and validation of interventions and their respective effectiveness in both prevention and rehabilitation of these traumatic knee injuries.